2019
DOI: 10.20944/preprints201906.0223.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Curcumin Attenuates Lead-Induced Cerebellar Toxicity in Rats via Inhibition of Oxidative Stress and Chelating Activity

Abstract: Lead (Pb) is a toxic environmental heavy metal that induces serious clinical defect on all organs with the nervous system being the primary target. Curcumin is the main active constituent of turmeric rhizome (Curcuma longa) with strong antioxidant and anti-inflammatory properties. This study is aimed at evaluating the therapeutic potentials of curcumin on Pb-induced neurotoxicity. Thirty six male Sprague Dawley rats were randomly assigned into five (5) groups with 12 rats in the control (normal saline) and 6 r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Previous studies on rats and humans have shown that exposure to lead could induce a series of pathological alterations resulting in serious health implications, manifesting different pernicious effects on multiple organs, particularly the brain (Abubakar, Mailafiya, et al, 2019; Rehman et al, 2018). These pernicious effects caused by lead intoxications may include redox homeostasis imbalance (Seddik et al, 2010; Sidhu & Nehru, 2004), cognitive impairments (Carrington et al, 2019), loss of motor coordination and paralysis (Mason et al, 2014), dullness and loss of memory (Vlasak et al, 2019), degeneration of neuronal cells, alteration of astrocyte maturation (Husain, 2015), and loss of integrity of blood–brain barrier (Beata et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on rats and humans have shown that exposure to lead could induce a series of pathological alterations resulting in serious health implications, manifesting different pernicious effects on multiple organs, particularly the brain (Abubakar, Mailafiya, et al, 2019; Rehman et al, 2018). These pernicious effects caused by lead intoxications may include redox homeostasis imbalance (Seddik et al, 2010; Sidhu & Nehru, 2004), cognitive impairments (Carrington et al, 2019), loss of motor coordination and paralysis (Mason et al, 2014), dullness and loss of memory (Vlasak et al, 2019), degeneration of neuronal cells, alteration of astrocyte maturation (Husain, 2015), and loss of integrity of blood–brain barrier (Beata et al, 2007).…”
Section: Discussionmentioning
confidence: 99%